To simplify the expression 6g - g, you first need to combine like terms. Like terms have the same variable raised to the same power. In this case, both terms have the variable g raised to the power of 1. When you subtract g from 6g, you are left with 5g. Therefore, the simplified form of 6g - g is 5g.
924/5 184.8
The answer is: 5g - 6
You take out the common factor, namely, "g".
In algebra, when you have an expression like 6g-g, you can simplify it by combining like terms. In this case, the "g" terms are like terms because they have the same variable. So, 6g-g simplifies to 5g, meaning you subtract the coefficient of the second term from the coefficient of the first term while keeping the variable the same.
5G - 5 = 100 5g = 100+5 5G = 105 G = 105 divided by 5 g = 21
5g - g = 4g
g equals 9If2g + 14 + 5g = 8g - 3 + 8then:7g + 14 = 8g + 5therefore7g - 8g = -14 + 5-g = -9g = 9.
To simplify the expression 6g - g, you first need to combine like terms. Like terms have the same variable raised to the same power. In this case, both terms have the variable g raised to the power of 1. When you subtract g from 6g, you are left with 5g. Therefore, the simplified form of 6g - g is 5g.
It is an equation in two variables, c and g.
3g+5g equals 8g when simplified
No 43 mg equals 0.043 g which is obviously less than 5 g.
5g is bigger because 5g = 5000 mg
the answeres 5g
No!
Because the value of g is 7 and 5*7 = 35
5g is the larger quantity.